Comparative Genomics Identifies the Genetic Islands That Distinguish Neisseria meningitidis, the Agent of Cerebrospinal Meningitis, from Other Neisseria Species - Perrin, Agnès (American Society for Microbiology, 2002)
Neisseria meningitidis colonizes the nasopharynx and, unlike commensal Neisseria species, is capable of entering the bloodstream, crossing the blood-brain barrier, and invading the meninges. The other pathogenic Neisseria species, Neisseria gonorrhoeae, generally causes an infection which is localized to the genitourinary tract. In order to investigate the genetic basis of this difference in disease profiles, we used a strategy of genomic comparison. We used DNA arrays to compare the genome of N. meningitidis with those of N. gonorrhoeae and Neisseria lactamica, a commensal of the nasopharynx. We thus identified sequences conserved among a representative set of virulent strains which are either specific to N. meningitidis or shared with N. gonorrhoeae but absent from N. lactamica. Though these bacteria express dramatically different pathogenicities, these meningococcal sequences were limited and, in contrast to what has been found in other pathogenic bacterial species, they are not organized in large chromosomal islands.